Assessment of indirect inflammatory markers in patients with myocardial bridging - Cerit, Levent (Cardiovasc J Afr, 2017)
INTRODUCTION: Myocardial bridging (MB) is a congenital variant of the coronary artery in which a portion of the epicardial coronary artery takes an intramuscular course. Although it is considered a benign anomaly, it may lead to such complications as myocardial ischaemia, acute coronary syndrome, coronary spasm, exercise-induced dysrhythmias or even sudden death. MB may be related to increased inflammatory and atherosclerotic processes. This study was conducted with the aim of evaluating the relationship between neutrophil/ lymphocyte ratio (NLR) and MB. METHODS: Taking into consideration the inclusion criteria, 86 patients with MB and 88 with normal coronary angiographies (control group) were included in the study. The association between MB and laboratory and other clinical parameters was evaluated. RESULTS: The platelet distribution width (PDW) (17.3 ± 0.40 vs 16.1 ± 0 .5; p < 0.05), NLR (3.2 ± 1.3 vs 2.2 ± 0.9; p < 0.05) and red cell distribution width (RDW) (14.3 ± 1.3 vs 13.1 ± 1.1; p < 0.05) were significantly higher in the MB group than in the control group. CONCLUSIONS: This study demonstrated that compared to normal coronary arteries, PDW, NLR and RDW were significantly higher in MB patients. Further studies are needed to clarify the increased inflammatory parameters in patients with MB.